Effect of Switching Atmospheric Conditions during Crystallization on the Phase Evolution of Solution‐Derived Lead Zirconate Titanate Thin Films. Issue 9 (13th August 2013) - Mhin, Sungwook; Cozzan, Clayton; Nittala, Krishna; Wanninkhof, Patrick; Ihlefeld, Jon F.; Brennecka, Geoff L.; Jones, Jacob L.; Trolier‐McKinstry, S.
<x xml:space="preserve">Abstract</x> The crystallization behavior of solution‐derived lead zirconate titanate (PZT) thin films in different atmospheric environments was studied using in situ X‐ray diffraction. The stability of the transient intermetallic Pt3Pb phase and perovskite PZT is dependent on oxygen partial pressure during crystallization. Based on the relationship between oxygen partial pressure and the resultant phase stability of intermediate phases, a new route to produce PZT thin films was developed. The new route involves switching atmospheres during crystallization and is shown to mitigate the formation of the transient intermetallic Pt3Pb phase and to promote the perovskite PZT phase. The route evidences a new and significant variable controlling film synthesis and film microstructure.